2019
DOI: 10.1016/j.ajodo.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

CAD-CAM–fabricated mini-implant insertion guides for the delivery of a distalization appliance in a single appointment

Abstract: This article reports on the technical aspects of using a computer-aided design-computer-aided manufacturing (CAD-CAM) insertion guide for the placement of orthodontic mini-implants used for the purpose of providing anchorage support for maxillary molar distalization. A 10-year-old girl presented with a bilateral full-step Angle Class II molar relationship in the permanent dentition, with anterior arch-length insufficiency and blocked out maxillary canine teeth. The primary treatment objective was to provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…The number of articles included may appear small given the overall literature on guided mini-implant insertion [34][35][36][37][38][39][40][41][42]. However, most papers are based on a very limited numbers of cases and lack appropriate control groups to adequately assess the potential benefits of using 3D surgical guides [18][19][20][21][22][23][24][43][44][45][46]. It should be taken into account that guide fabrication makes guided mini-implant procedures more expensive and more time-consuming than direct manual insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The number of articles included may appear small given the overall literature on guided mini-implant insertion [34][35][36][37][38][39][40][41][42]. However, most papers are based on a very limited numbers of cases and lack appropriate control groups to adequately assess the potential benefits of using 3D surgical guides [18][19][20][21][22][23][24][43][44][45][46]. It should be taken into account that guide fabrication makes guided mini-implant procedures more expensive and more time-consuming than direct manual insertion.…”
Section: Discussionmentioning
confidence: 99%
“…De Gabriele et al superimposed a plaster cast on a CBCT image to identify optimal sites for mini-implant placement in the anterior hard palate [7]. In this context, Wilmes et al reported that superimposition with lateral cephalometric radiographs is also possible [27]. After virtual placement planning, a surgical insertion guide, called Easy Driver, was produced by rapid prototyping, which allowed for insertion through the guide using a special contra-angle screwdriver.…”
Section: Sd Standard Deviationmentioning
confidence: 99%
“…In this context, Wilmes et al demonstrated the possibility of superimposition with lateral cephalograms [27]. Cassetta et al performed postoperative CBCT after OMI placement and compared results with preoperative planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 To overcome the loss of anchorage produced by intraoral appliances, temporary skeletal anchorage devices were placed palatally to support these appliances. [10][11][12][13] In addition, a new appliance called a zygoma gear, consisting of titanium plates placed in the zygomatic process of the maxilla, was described for bilateral maxillary molar distalization without inducing anchorage loss or depending on patient compliance. 14 Several studies have reported the treatment effects of this approach.…”
mentioning
confidence: 99%